A (DE)SACRALIDADE DA VIDA EM SEIS NARRATIVAS CURTAS DE RUBEM FONSECA - Alves, Adriano Rodrigues (2015)
This aim of this study is to understand, due to the assumptions of comparative literature, the sacredness of life on the fictional construction, problematizing the intersubjective relations of the characters and their interactions in the urban environment of Rubem Fonseca s literary works. In order to achieve this, besides the specific contributions of literary approach, contributions of anthropology and philosophy were used. The study was based on three short stories of Amálgama (2013) and three short stories of Axilas e outras histórias indecorosas (2011a). The presupposition is that the Literature helps us to question the world that surround us, because the form and the content of the narrations are interrelated. Rubem Fonseca s short stories approach events which, at first glance, refer to an idea of the violence trivialization in different social areas, but the main idea is the questioning about the meaning of life and its ambiguities. In this regard, the emphasized violence on the short stories highlights its contrary, what is outside them and what dialogues with them: the sacredness of life. For the theoretical approach to the subject of the sacredness of life, we chose the reflections about homo sacer, over paper the "scapegoated" in the relationship between the sacred and violence and about biopolitics.